THE IMPLEMENTATION OF TECHNOLOGY ACCEPTANCE MODEL IN ANALYZING ATTITUDES TOWARD THE ADOPTION OF FINTECH - Natsir, Khairina; Arifin, Agus Zainul; Darmawan, Herie (International Journal of Application on Economics and Business, 2023)
The intention of this study is to find empirical prooving regarding the relationship model of Perceived Risk, Perceived Ease-of-Use, and Perceived Usefulness against Attitudes Toward the Adoption of FinTech, by adopting the Technology Acceptance Model theoretical approach. The source of the data used is primary data derived from questionnaires which are distributed directly to respondents using a questionnaire with a Google Form format. Respondents are limited to users of banking services and marketplaces who are domiciled in Jakarta and its surroundings. Data were collected using non-probability sampling method. The instrument used is a structured questionnaire of 14 questions which are arranged based on indicators and dimensions derived from each variable. This study uses the multiple regression method with the support of the Smart PLS version 3. The finding of this study show that Perceived Risk, Perceived Ease-of-Use, and Perceived Usefulness have a positive effect on Attitudes Toward the Adoption of FinTech Services.